Human Adenovirus Serotype 3 Infection Modulates the Biogenesis and Composition of Lung Cell-Derived Extracellular Vesicles. (9th December 2021) - Ipinmoroti, Ayodeji O.; Crenshaw, Brennetta J.; Pandit, Rachana; Kumar, Sanjay; Sims, Brian; Matthews, Qiana L.
Abstract : Adenovirus (Ad) is a major causal agent of acute respiratory infections. However, they are a powerful delivery system for gene therapy and vaccines. Some Ad serotypes antagonize the immune system leading to meningitis, conjunctivitis, gastroenteritis, and/or acute hemorrhagic cystitis. Studies have shown that the release of small, membrane-derived extracellular vesicles (EVs) may offer a mechanism by which viruses can enter cells via receptor-independent entry and how they influence disease pathogenesis and/or host protection considering their existence in almost all bodily fluids. We proposed that Ad3 could alter EV biogenesis, composition, and trafficking and may stimulate various immune responses in vitro . In the present study, we evaluated the impact of in vitro infection with Ad3 vector on EV biogenesis and composition in the human adenocarcinoma lung epithelial cell line A549. Cells were infected in an exosome-free media at different multiplicity of infections (MOIs) and time points. The cell viability was determined using 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl tetrazolium bromide (MTT) and fluorometric calcein-AM. EVs were isolated via ultracentrifugation. Isolated EV proteins were quantified and evaluated via nanoparticle tracking, transmission electron microscopy, sodium dodecyl sulfate-polyacrylamide gel electrophoresis, and immunoblotting assays. The cell viability significantly decreased with an increase in MOI and incubation time. A significant increase in particle mean sizes, concentrations, and total EV protein content was detected at higher MOIs when compared to uninfected cells (control group). A549 cell-derived EVs revealed the presence of TSG101, tetraspanins CD9 and CD63, and heat shock proteins 70 and 100 with significantly elevated levels of Rab5, 7, and 35 at higher MOIs (300, 750, and 1500) when compared to the controls. Our findings suggested Ad3 could modulate EV biogenesis, composition, and trafficking which could impact infection pathogenesis and disease progression. This study might suggest EVs could be diagnostic and therapeutic advancement to Ad infections and other related viral infections. However, further investigation is warranted to explore the underlying mechanism(s).